Peran Patroli Polisi Dalam Upaya Pencegahan Dan Penanggulangan Kejahatan Pada Polres Banyuwangi - Nugroho, Handoko Ardhi; Wulan, Retno; Susanto, Dedi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The research method used is qualitative and then presented in a descriptive way, namely by parsing, summarizing, and describing cases that are familiar with this research. This research was carried out at the Gowa Police Station, by interviewing the Police, especially the Traffic Base and the Sabhara Basis. The use of qualitative analysis methods covers all the information that has been obtained, thus supporting the qualifications of this observation. The research results show that there are 4 forms of langlang carried out by the Gowa Police Police, namely walking langlang, bicycle langlang, motorbike langlang, and car langlang. The most regularly carried out trips are motorbike and car trips because they are more efficient in providing services to the community. The hindering aspects are the lack of square personnel, the increasing number of errors from year to year, the equipment and infrastructure that are still lacking and the residents not participating in maintaining security and discipline.